Merjenje družbenoekonomskih učinkov znanstvenih raziskav v športu - izzivi in smeri razvoja - Čadež, Simon (Šport (Ljubljana), 2023)
Two contemporary problems in scientific research are the segregation of knowledge creation and research productivity as well as the inability to demonstrate the value for money of public research funding. More and more countries are therefore moving from a strategy of increasing “research productivity” to one of increasing the “socio-economic impact” of scientific research. This shift in strategy is inevitably linked to the development of models for measuring the socio-economic impact of science, which are cur- rently still under development. This paper analyses the challenges in developing such models and the direction of development. We conclude that the development of more sophisticated models is inevitable, as policymakers want a tool that would allow for an optimal allocation of research resources between fields in terms of their contribution to welfare.
Keywords: raziskave; raziskovalna politika; razvoj; šport; znanstveno raziskovanje